Edukasi dan Pelatihan Pembuatan PMT Gluten Free untuk Balita pada Kader Posyandu Desa Purbayan, Sukoharjo - Laela Rokhmah; Binardo Adi Seno (Yayasan Sumber Daya Manusia Cerdas, 2024)
Posyandu (integrated Service Post) is the government's effort to make it easier for the Indonesian people to obtain cadres who are implementers in the field in posyandu activities. This cadre consists of mothers who are tasked with running and ensuring that posyandu activities run smoothly. PMT (Providing Additional Food) is one of the efforts of posyandu cadres to educate and provide adequate nutrition to toddlers. Gluten free is needed to accommodate toddlers who suffer from celiac disease. The aim of this activity is to provide education to the cadets about the importance of gluten-free PMT innovation and also train them in making PMT. This activity is filled with socialization and training on making PMT. After this activity, 93,10% of cadres knew the meaning of gluten free and 96,5% knew the reasons for providing gluten free PMT. 100% of cadres can make PMT creations from gluten free ingredients.